Disasters and Refugee Protection: A Socio-legal Case Study from Yemen - Vikram Kolmannskog (Oslo Law Review)
Abstract Every year millions of people are forced to flee their homes in the context of climate change and disasters. Their needs and rights are unclear. This paper presents and discusses some findings from a socio-legal case study exploring the rights of disaster-affected Somalis and Ethiopians in Yemen. The first main findings relate to the challenges that Ethiopians faced in accessing, and succeeding with, the formal asylum process. This is discussed in light of legal aid theory and research as well as research on credibility assessments. Another category of findings relates to interactions of local, religious law and international law. This is discussed in light of legal pluralism, which helps in identifying an emancipatory potential. While complex, dynamic and dependant on regional politics and other factors, the way Islamic law was applied — and influenced other bodies of law — seemed to ensure better protection than the 1951 Refugee Convention alone. This potential should be further explored and possibly expanded in order to strengthen the rights of people displaced in the context of climate change and disasters more generally.